2001
DOI: 10.1034/j.1600-0749.2001.140506.x
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Melanogenic Response of Human Melanocytes in Mono‐culture, in Co‐Culture with Keratinocytes and in Reconstructed Epidermis, to UV Exposure

Abstract: Striking differences are observed in the melanogenic response of normal human melanocytes to UVA and UVB irradiation depending on culture conditions and the presence of keratinocytes. Exposure of melanocytes co-cultured with keratinocytes to UVB irradiation triggered, already at low doses (5 mJ/cm2), an increase in melanin synthesis whereas in melanocyte mono-cultures, UVB doses up to 50 mJ/cm2 had no melanogenic effect. Unlike UVB, UVA exposure caused the same melanogenic response in both mono- and co-culture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
66
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(78 citation statements)
references
References 31 publications
(36 reference statements)
4
66
0
Order By: Relevance
“…However, that melanocyte culture model does not reflect the effects of putative bioactive compounds on keratinocytes (or other cell types) that might indirectly affect melanocyte function (such as might occur in the skin). In recent years, various pigmented human skin equivalents have been reconstituted and used to evaluate melanocyte responses to environmental stimuli (9,20,22,(32)(33)(34)(35)(36). Although such skin equivalents more effectively mimic the physiologic situation of normal human skin, they are not suitable for extensive screening of potential melanogenic compounds due to their expense and the time and effort required to set up and maintain them.…”
mentioning
confidence: 99%
“…However, that melanocyte culture model does not reflect the effects of putative bioactive compounds on keratinocytes (or other cell types) that might indirectly affect melanocyte function (such as might occur in the skin). In recent years, various pigmented human skin equivalents have been reconstituted and used to evaluate melanocyte responses to environmental stimuli (9,20,22,(32)(33)(34)(35)(36). Although such skin equivalents more effectively mimic the physiologic situation of normal human skin, they are not suitable for extensive screening of potential melanogenic compounds due to their expense and the time and effort required to set up and maintain them.…”
mentioning
confidence: 99%
“…Studies have shown that UV irradiation induces the production of melanogenic stimulators such as nitric oxide, endothelin 1,␣-melanocyte-stimulating hormone, adrenocorticotropic hormone, and prostaglandin E2 (5,6,7). In vivo reflectance confocal imaging of murine skin following exposure to UVB light highlighted its effect on the dendricity of melanocytes (8).…”
mentioning
confidence: 99%
“…Although UVB exposure results in a delayed pigmentation response that occurs many hours to days later (22), brief UVA exposure leads to a rapid and transient response within minutes via a largely unknown mechanism (23,24). Because UVA penetrates skin more deeply than UVB, HEMs, located in the basal layer of the epidermis, are exposed to significantly more UVA than UVB (25,26). Because our UVR-stimulation source contains ∼90% UVA and ∼10% UVB, we compared the photocurrent amplitude in response to 250 mJ/cm 2 UVR to the components 25 mJ/cm 2 UVB or 225 mJ/cm 2 UVA.…”
mentioning
confidence: 99%